2011
DOI: 10.1016/j.yjmcc.2011.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule Wnt inhibitors enhance the efficiency of BMP-4-directed cardiac differentiation of human pluripotent stem cells

Abstract: Human induced pluripotent stem (iPS) cells potentially provide a unique resource for generating patient-specific cardiomyocytes to study cardiac disease mechanisms and treatments. However, existing approaches to cardiomyocyte production from human iPS cells are inefficient, limiting the application of iPS cells in basic and translational cardiac research. Furthermore, strategies to accurately record changes in iPS cell-derived cardiomyocyte action potential duration (APD) are needed to monitor APD-related card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 40 publications
3
101
0
Order By: Relevance
“…Our results and prior studies (21)(22)(23)(24) indicate that early induction of canonical Wnt signaling and suppression of canonical Wnt signaling at later stages of differentiation synergistically enhance yield of cardiomyocytes with other growth factors and/or serum. We next sought to determine whether modulating regulatory elements of Wnt signaling alone, in the absence of serum and exogenous growth factors, was sufficient to induce cardiogenesis.…”
Section: Highly Efficient Generation Of Human Cardiomyocytes Solely Bysupporting
confidence: 71%
“…Our results and prior studies (21)(22)(23)(24) indicate that early induction of canonical Wnt signaling and suppression of canonical Wnt signaling at later stages of differentiation synergistically enhance yield of cardiomyocytes with other growth factors and/or serum. We next sought to determine whether modulating regulatory elements of Wnt signaling alone, in the absence of serum and exogenous growth factors, was sufficient to induce cardiogenesis.…”
Section: Highly Efficient Generation Of Human Cardiomyocytes Solely Bysupporting
confidence: 71%
“…Tnks and Porcn inhibitors, including IWR-1 and IWP-2, are now widely used for the in vitro engineering of various tissues, including cardiomyocytes, retinal pigmented epithelial cells, pneumocytes, and dopaminergic neurons (40)(41)(42)(43)(44)(45)(46)(47). Given the transient nature of the chemical exposure in these protocols (typically 2 to 3 days) and similar efficacies of Tnks and Porcn inhibitors for directing cell fate in a direct comparison (46), we assume the chemical induction of these cell types is due to suppression of Wnt/␤-catenin transcriptional responses and not telomeric stress or shortening.…”
Section: Discussionmentioning
confidence: 99%
“…IWP-4 and IWR-1 act by inhibiting the palmitylation of WNT proteins by porcupine (PORCN), a membrane-bound O-acyltransferase, thereby blocking WNT secretion and activity (Chen et al, 2009a). An additional study demonstrated that following BMP4-treatment of hESCs and hiPSCs, IWR-1 significantly improved cardiomyocyte differentiation resulting in cells with typical electrophysiological functions and pharmacological responsiveness (Ren et al, 2011). An interesting recent study demonstrated that successive, mutually exclusive waves of non-canonical and canonical WNT signalling precede mesoderm differentiation, and blocking these two waves leads to differential differentiation (Rai et al, 2011).…”
Section: Wnt Pathway-mediated Hesc Differentiationmentioning
confidence: 99%
“…WNT Cardiomyocytes (Hudson et al, 2011) IWR-1 WNT Cardiomyocytes (Ren et al, 2011) IWR-1, IWP-3 WNT Cardiomyocytes (Willems et al, 2011) LY294002 PI3K PI3K/AKT/mTOR Endodermal (Touboul et al, 2010) Myocyte progenitors (Mahmood et al, 2010) hESC-derived hemogenic epithelial cells into HPCs (Wang et al, 2011) Cardiomyocytes (Graichen et al, 2008;Xu et al, 2008), Endothelial cells (James et al, 2010).…”
Section: Iwp-4 Iwr-1mentioning
confidence: 99%